2021
DOI: 10.3390/app11188446
|View full text |Cite
|
Sign up to set email alerts
|

Modified Endoscopic-Assisted Approach for Removal of Ectopic Third Molar in the Maxillary Sinus

Abstract: This case series describes an alternative approach for removing ectopically erupted tooth in the maxillary sinus using an improved endoscopic approach known as modified endoscopic-assisted sinus surgery (MESS). We reviewed medical charts and radiographs of patients who underwent surgical removal of an ectopic tooth in the maxillary sinus using MESS. The surgical technique consisted of creating a bony window in the maxillary sinus wall with a pre-adapted microplate, which was repositioned after the tooth was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…8 The main advantage of MESS is that the physiological functions of paranasal sinus are maintained while avoiding the formation of postoperative maxillary cysts or sinus scar tissues. 7 A previous study by Han et al 9 demonstrated the successful outcomes of MESS through histopathologic and ultrastructural findings indicating the regeneration of SM and complete bone healing with clinical restoration of maxillary sinus functions that were achieved optimally 6 months after the treatment. 9 Periodic radiographs and clinical follow-ups are important to ensure that the maxillary sinus is normalized before proceeding with implant treatment.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…8 The main advantage of MESS is that the physiological functions of paranasal sinus are maintained while avoiding the formation of postoperative maxillary cysts or sinus scar tissues. 7 A previous study by Han et al 9 demonstrated the successful outcomes of MESS through histopathologic and ultrastructural findings indicating the regeneration of SM and complete bone healing with clinical restoration of maxillary sinus functions that were achieved optimally 6 months after the treatment. 9 Periodic radiographs and clinical follow-ups are important to ensure that the maxillary sinus is normalized before proceeding with implant treatment.…”
Section: Discussionmentioning
confidence: 93%
“…We used MESS before implant rehabilitation as the treatment of choice for our 9 cases with various entities including odontogenic maxillary sinusitis, OAF, mucous retention cyst (MRC), fungal maxillary sinusitis, and oronasal fistula. MESS versatile application has been reported in several articles for the intraoral reduction of blowout orbital fractures,5 management of MRC,6 removal of ectopic third molar in the maxillary sinus,7 and removal of implant beneath the optic canal 8. The main advantage of MESS is that the physiological functions of paranasal sinus are maintained while avoiding the formation of postoperative maxillary cysts or sinus scar tissues 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After a first screening of the titles and abstracts, a total of porting results of clinical studies on patients that underwent oral surgery combination with the use of the bone lid technique were selected. After eva full-text of these articles, 21 of them were excluded [7,8,13,16,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45] for exclusion are listed in Table 2. A total of 20 studies published in the ye were included.…”
Section: Resultsmentioning
confidence: 99%
“…Although these transnasal endoscopic approaches may appear to allow easy access to identify and remove the foreign body from the maxillary sinus, it can be difficult to remove or even identify displaced dental implants that are located in the anteroinferior part of the sinus [ 7 , 11 , 13 , 14 ]. In contrast, the MESS approach can overcome this complication and identify the migrated dental implant in any part of the sinus with endoscopic assistance through a bony window placed in the anterolateral wall [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%